Motivational and myopic mechanisms underlying dopamine medication-induced impulsive-compulsive behaviors in Parkinson's disease - Dawson, Andrew; Ortelli, Paola; Carter, Adrian; Ferrazzoli, Davide; Dissanayaka, Nadeeka N.; Evans, Andrew; Chye, Yann; Lorenzetti, Valentina; Frazzitta, Giuseppe; Yücel, Murat (Frontiers in Behavioral Neuroscience, 2023)
Dopaminergic medications can trigger impulsive-compulsive behaviours (ICBs) in predisposed Parkinson’s disease (PD) patients, but what this implies on a neurocognitive level is unclear. Previous findings highlighted potentially exacerbated incentive motivation (willingness to work for rewards) and choice impulsivity (preferring smaller, immediate rewards over larger, delayed rewards) in PD patients with ICBs (PD+ICBs). To deeply understand this evidence, we studied 24 PD+ICBs and 28 PD patients without ICBs (PD-ICBs). First of all, patients underwent the assessment of Impulsivity Traits, mood, anxiety, and addiction condition. We further administered robust objective and subjective measures of specific aspects of motivation. Finally, we explored whether these processes might link to any heightened antisocial behaviour (aggression and risky driving) in PD+ICBs. Results revealed that high levels of Positive Urgency Trait characterized PD+ICBs. They choose to exert more effort for rewards under conditions of low and medium reward probability and as reward magnitude increases. Findings on choice impulsivity show a great tendency to delay discounting in PD+ICBs, other than a high correlation between delay and probability discounting. In addition, we found what appears to be the first evidence of heightened reactive aggression in PD patients with ICBs. Exacerbated incentive motivation and delay discounting trended towards positively predicting reactive aggression in PD+ICBs. Our promising results suggest that there might be immense value in future large-scale studies adopting a transdiagnostic neurocognitive endophenotype approach to understanding and predicting the addictive and aggressive behaviours that can arise from dopaminergic medication in PD.